The Relationship between Mental Health and the Functional Performance of High School Physical Education and Sports Teachers’ (Field Study among some High Schools in M’sila State) - Toumiat , abderrazak; laznak , ahmed (Journal of Social Sciences and Humanities, 2021)
The current study aims to explore the relationship between mental health, the physical and functional performance of physical education and sport teachers in high schools and to reveal their level of mental health as well as their level of performance. The researcher relies up on the analytical descriptive method. The study sample includes twenty (20) teachers of physical education and sport in M'sila high schools (During 2018/2019 season). The tools which the researcher uses are the following: Mental health scale and questionnaire of functional performance evaluation. The statistical treatment carries out through the statistical package that ends with the following results: Physical education and sport teachers have good mental health. And there are varying levels of athletic and functional performance among them, in each of (lesson design, lesson implementation, evaluation, classroom organization and management). There are different levels of functional performance for Physical education and sport teachers in high schools. Some of the main suggestions: explore the other models that tackled the relationship between mental health and performance. Conduct studies about the mental health of physical education and sport teachers among other levels (intermediate, training centers and the university). We suggest that the measure of mental health that we have prepared to be a model that can be relied upon in practical studies and in determining the level of mental health for teachers of physical education and sports.